Pelatihan Peningkatan Kemampuan Kader dalam Deteksi Dini dan Rujukan Kasus Kehamilan Risiko Tinggi - Lailiyana, Lailiyana; Fitri, Fitri; Magdalena, Magdalena (Universitas Pahlawan Tuanku Tambusai, 2026)
In Indonesia, approximately 15–20 percent of pregnancies and deliveries are prone to complications, and the risk increases if the mother has comorbidities or certain risk factors. These conditions are not only dangerous for the mother, but also for the fetus, and can even increase the risk of death. This community service activity aimed to improve the ability of Posyandu cadres to detect early and refer high-risk pregnancy cases in Ranah Singkuang Village, the working area of the Air Tiris Community Health Center in Kampar District. The training was attended by 15 Posyandu cadres through the delivery of material on risky pregnancies, the use of the Puji Rochyati Score Card (KSPR), and the referral mechanism. In addition to the material delivery, practical guidance on risk factor assessment using the KSPR was also provided. The results showed an increase in cadres' knowledge, with an average post-test score of 91.55 compared to a pre-test score of 79.11. The cadres were also assessed as capable of filling out the KSPR form correctly. The health center was advised to continue the guidance to ensure that community-based early detection remains sustainable.